'Crooked roads without improvement': Rhyming and Unrhyming in Blake. Issue 2 (July 2017) - Kellett, Lucy
Abstract : This essay posits rhyme as an important locus of invigorating 'Contraries' in Blake's spiritual ideology and poetic practice. It explores tensions in Blake's conception of rhyme as unthinking abandon and over-reasoning rigidity, a trivialising indulgence yet rife with Urizenic implications. Moving through the Poetical Sketches and Songs to the climactic epic Jerusalem, we see how Blake seeks greater formal freedom in more capacious – or 'crooked' – poetic lines, aiming to embody the unrehearsed voice of a 'true Orator' and avoid passive 'Sing Song' reading. But Blake also frequently exploits the fixity of formal rhyme schemes to dramatically enact the oppressiveness of 'enclos'd' mindsets, so that the 'bounding lines' of his form often pivot between expressing and imposing ideas of order that bespeak both technical precision and limitation. The essay goes on to consider Blake's use of repetition in particular as one means of reconciling the paradoxes flung up by the presence and absence of rhyme throughout his canon.